RELATIONSHIP BETWEEN USE OF LEARNING MEDIA WITH THE MATHEMATICS LEARNING OUTCOMES OF SMK N 3 BONDOWOSO STUDENTS - Sielfiana, Sielfiana; Wardono, Danu; Sriwiyanti, Netty; Pratiwi , Sukma Restuning (Journal of Education Technology and Inovation, 2023)
The purpose of this study was to find out the relationship between student learning outcomes in mathematics and the use of learning media. The sample for this research was selected from as many as 34 students in class X by using cluster random sampling techniques, namely quantitative and correlation techniques. Questionnaires and learning achievement tests serve as data collection instruments. Data analysis is used, especially direct correlation analysis. This technique determines the significance of the correlation between the variables studied. Normality and linearity tests, which are prerequisite tests for this method, were used. The research findings show that there is a relationship between the use of instructional media and student learning outcomes. This is due to the 0.617 correlation between the use of educational media and student learning outcomes. The fact that the value of 0.617 is in the range of 0.61-0.80 indicates the strength of the relationship. However, the direction of the relationship is favorable because the value of r is favorable